OVARIAN STIMULATION WITH FOLLITROPIN-δ REDUCES RISK OF OVARIAN HYPERSTIMULATION SYNDROME: Follitropin-δ reduces Ovarian Hyperstimulation Syndrome risk - Perovic, Milan; Zecevic, Nebojsa; Bojovic Jovic, Dragana; Nozic Zecevic, Tatjana; Stojsavljević, Aleksandar; Nikolic, Gorana; Nikolic, Ana (Medical Research, 2024)
INTRODUCTIONOvarian stimulation (OS) during assisted reproductive technology (ART) carries the risk of ovarian hyperstimulation syndrome (OHSS). The risk is increased in polycystic ovary syndrome (PCOS). Recombinant DNA technologies have brought new generations of gonadotropins, such as Follitropin-δ. Individualized Follitropin-δ dosing, based on patient’s body weight (BW) and AntiMuellrian hormone (AMH), reduces OHSS risk.AIMTo compare prevalence of OHSS and efficacy of OS with individualized Follitropin-δ and standard dosing with old generation gonadotropins in women with PCOS.MATERIAL AND METHODSCase-control study encompassed 24 women stimulated with individualized Follitropin-δ dosing (Study Group) and 48 women with standard old generation gonadotropin dosing (Control Group). Inclusion criteria: PCOS. Exclusion criteria: other causes of infertility. Study participants were matched according to age, BW, AMH and smoking status.RESULTSPrevalence of moderate (0% vs. 5.9%) and severe (0% vs. 17.6%) OHSS were significantly lower in Study Group (p=0.009). Duration of OS (9.06±1.53 vs. 10.00±1.13 days, p=0.01) and total gonadotropin dose (1,117.95±234.90 vs. 1,940.33±501.20 IU, p